2014
DOI: 10.1117/1.jbo.19.8.087007
|View full text |Cite
|
Sign up to set email alerts
|

Use of reflectance near-infrared spectroscopy to investigate the effects of daily moisturizer application on skin optical response and barrier function

Abstract: Citation: Qassem, M. & Kyriacou, P. A. (2014). Use of reflectance near-infrared spectroscopy to investigate the effects of daily moisturizer application on skin optical response and barrier function. Journal of Biomedical Optics, 19(8), 087007. doi: 10.1117/1. JBO.19.8.087007 This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract. A number of noninvasive techniques and instruments have emerged over the years allowing much progress towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…Exceptions to this are NIR spectroscopy and OTTER. NIR spectroscopic instrumentation can be easily coupled with flexible fibre optics and portable spectrometers for reduced costs and restrictions on selection of examination site, and can offer increased stability against environmental conditions such as temperature and relative humidity [248, 250,257]. Moreover, techniques such as ATR-IR are occlusive, which can cause accumulation of water at the test site, and as for OCT, the coherence length is short, and resolution can be less than 10 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exceptions to this are NIR spectroscopy and OTTER. NIR spectroscopic instrumentation can be easily coupled with flexible fibre optics and portable spectrometers for reduced costs and restrictions on selection of examination site, and can offer increased stability against environmental conditions such as temperature and relative humidity [248, 250,257]. Moreover, techniques such as ATR-IR are occlusive, which can cause accumulation of water at the test site, and as for OCT, the coherence length is short, and resolution can be less than 10 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a series of studies by Qassem et al [250][251][252][253] combined NIR data with both PCR and PLS techniques and found clear spectral differences associated with frequency of moisturiser use ( Figure 6), and highlighted the possibility of using this technique to detect changes in barrier function by measuring water penetration after wet patch testing. The authors suggested that NIR spectroscopy can provide comprehensive skin analysis in a fast and simple manner.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…As for the NIR skin spectra, the same instrumental settings described in our previous publication 18 were maintained in order to avoid changes relating to technical differences.…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%
“…Using this information, it can be assumed that changes to skin barrier function can be detected by monitoring differences in absorption at the two bands over time. In a previous study, 18 we used principal component analysis (PCA) to demonstrate a clear link between separation and randomization of PCA scores with the frequency of moisturizer application. Additionally, in a pilot study implementing a different protocol, 19 similar results were obtained, and the change in absorption intensity at the 1450 and 1900 nm bands prior to and following regular moisturizer application were taken to suggest that long-term moisturizer use had limited water uptake from deeper penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Water, in particular, has several prominent absorption peaks in the NIR spectrum. These properties can be used to deduce information pertaining to various aspects of skin health [8,9,10,11]. Interestingly, it is possible to differentiate between bound and free water inside the skin [12].…”
Section: Introductionmentioning
confidence: 99%